A BIM–LCA integration technique to embodied carbon estimation applied on wall systems in Brazil. Issue 5 (12th November 2018) - Crippa, Julianna; Boeing, Letícia Cavassin; Caparelli, Ana Paula Angonese; da Costa, Marienne do Rocio de Mello Maron; Scheer, Sergio; Araujo, Aline Medeiros Ferreira; Bem, Diogo
Abstract : Purpose: Aiming to simplify the extraction of embodied carbon data using a building information modeling (BIM) software, the purpose of this paper is to present a framework that integrates BIM and life cycle assessment (LCA), which are useful to the architecture, engineer and construction (AEC) industry. As a further purpose, this study also tests four different wall systems. Design/methodology/approach: The study applies design science research and it presents a framework that integrates BIM and LCA. For analysis and validation, a case study features four different wall systems costs based on the Brazilian context. In the proposed framework, SimaPro8 accomplishes the LCA, while ArchiCAD 19 the modeling. Findings: The first analysis covers embodied carbon and the second covers the total cost of each m² of wall. The proposed framework performs well, and it is effective in the Brazilian context. Concerning the walls, the wood frame system is the most sustainable option within this analysis and the most financially feasible option in Brazil. Originality/value: The present study contributes to embodied carbon data analysis, ensuring that the best choice of elements and components is being used in the building project. This BIM–LCA integrated solution is valuable not only to the AEC industry and to professionals, but also to future researchers. This analysis is of great value to new ventures, since the society shows a great concern about reducing GHGs emissions.